Pengaruh Komitmen Organisasi dan Kompensasi Terhadap Organizational Citizenship Behavior (OCB) Melalui Motivasi Sebagai Variabel Intervening (Studi Pada Dinas Kependudukan dan Pencatatan Sipil Kota Malang) - Dodik Kurniawan; Agus Widarko; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe development of the era of globalization and the industrial revolution 4.0 is a challenge for organizations to be able to improve the quality of their human resources. The Covid-19 pandemic, which has changed all aspects of employment activities, has made employees have to be able to adapt to new online-based work systems. This study aims to determine the direct effect of organizational commitment, compensation and motivation on organizational citizenship behavior and motivation as an intervening variable. The population in this study amounted to 148 employees with a purposive sampling technique of 79 contract employees. Using path analysis, and the research results show that organizational commitment has a direct effect on motivation, compensation has a direct effect on motivation, organizational commitment has a direct effect on organizational citizenship behavior, compensation has no direct or indirect effect on organizational citizenship behavior, motivation has a direct effect on organizational citizenship behavior , motivation cannot mediate the effect of organizational commitment on organizational citizenship behavior, motivation can only mediate the effect of compensation on organizational citizenship behavior. Keywords : Organizational Commitment, compensation, motivation and organizational citizenship behavior.